Penyuluhan Peranan Perguruan Tinggi untuk Meningkatkan Kesejahteraan Masyarakat Nagari Sungai Limau Kabupaten Padang Pariaman - Marshal Imar Pratama; Mexano Hans Gery; Nichy Oktaviani; Asrul, Asrul; Sudirman, Sudirman; Anwar Rahim (CV. ITTC INDONESIA, 2025)
This community service activity, which focused on educating participants about the role of higher education in improving the welfare of the Sungai Limau community in Padang Pariaman Regency, aims to foster enthusiasm among participants to pursue higher education and increase public knowledge about higher education. Currently, many residents of Sungai Limau are from lower-middle income groups, so this outreach program is needed to open their minds to improving their welfare through a better economy. The community of Sungai Limau was very enthusiastic in attending this activity, and the event proceeded smoothly and received a positive response from the local government.